Teachers upgrading to favour the environmental dimension in Physical Education lesson for sixth grader students of Pinar del Rio Municipality - Margelia Bárbara Ramírez-Blanco; Maidelin Díaz-Miranda; Marilin Páez-Basabe (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2015)
The research that is presented proposes a training program for the professo rs of Physical Education that favours the introduction of the environmental dimension in the class for senior high school students of Pinar del Río municipality, to improve this training process related with the Environmental Education, the objective of the preparation is to offer the professors of Physical Education the necessary knowledge that it allows them to eliminate the obstacle that represents the lack of professional competitions for the construction of the environmental dimension because when obtaining the professor bigger knowledge it can fulfil its function better the pupil. With the objective of determining the insufficiencies in relation to the envi ronmental work, as well as to know the way of upgrading that was been using at the moment of the research there were applied scientific methods as observation, to Physical Education lessons and interview to Physical Education teachers and officials, who d eclared that there are not orientations in Physical Education syllabus to develop environmental education, it was verified there was a poor development of the didactic integrating conception of it, as well as a lack of documents and methodological and pre cise orientations. The designed program has 40 lesson hours, it is developed in three themes and y it is adapted to the new tendencies of competitions that mark the new laws of the education and structured in Thematic Plan, System of knowledge, Abilities, Securities to develop, methodological Orientations for its use and Evaluation.